2016
DOI: 10.1002/elps.201500504
|View full text |Cite
|
Sign up to set email alerts
|

Lipoaspirate fluid proteome: A preliminary investigation by LC-MS top-down/bottom-up integrated platform of a high potential biofluid in regenerative medicine

Abstract: The lipoaspirate fluid (LAF) is emerging as a potentially valuable source in regenerative medicine. In particular, our group recently demonstrated that it is able to exert osteoinductive properties in vitro. This original observation stimulated the investigation of the proteomic component of LAF, by means of LC-ESI-LTQ-Orbitrap-MS top-down/bottom-up integrated approach, which represents the object of the present study. Top-down analyses required the optimization of sample pretreatment procedures to enable the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…In our study, liposculpture of the area was performed after the excision, in order to obtain better skin redraping and to avoid irregularities. We believe that liposuction can play a key role in the final step of this procedure, with the goal of minimizing any irregularities [19,20]. After the resection, the surgeon can properly evaluate the stored area of fatty tissue and the presence of any unpleasant, irregular defects.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, liposculpture of the area was performed after the excision, in order to obtain better skin redraping and to avoid irregularities. We believe that liposuction can play a key role in the final step of this procedure, with the goal of minimizing any irregularities [19,20]. After the resection, the surgeon can properly evaluate the stored area of fatty tissue and the presence of any unpleasant, irregular defects.…”
Section: Discussionmentioning
confidence: 99%
“…Together with them, a panel of four peptides with molecular weight of about 3 kDa and corresponding to specific sequences of both aand b-globin chains has also been identified. These peptides, whose biological function is still not clear, have also been characterized in lipoaspirate fluid (Inserra et al 2016) and craniopharyngioma adamantinomatous pediatric brain tumor intracystic fluid (Martelli et al 2014). These peptides have been previously isolated in lysates of human erythrocytes (Karelin et al 1995).…”
Section: Hemoglobin Cryptidesmentioning
confidence: 99%
“…We have previously demonstrated that this fluid is able to exert angiogenic and osteoinductive properties in vitro [55]. We have further investigated the proteome-peptidome composition of LAF through a top down/bottom up approach [68]. This study allowed identifying numerous bioactive proteins, peptides and paracrine factors, such as albumin and hemoglobin fragments (i.e.…”
Section: Osteoinductive Properties Of Ascsmentioning
confidence: 99%
“…The LAF also featuredS100A6, a member of the S100 Ca 2+ -binding protein family. S100A6 induces bone formation modulating the capability of cells to sense extracellular cations [68].The documented presence ASC-like cells and bioactive molecules in the LAF, along with its rapid and easy isolation, make this fluid attractive and suitable for regenerative medicine applications, specifically as a "minimally manipulated tissue" to be tested in vivofor a potentially wide range of applications.…”
Section: Osteoinductive Properties Of Ascsmentioning
confidence: 99%